2010
DOI: 10.1111/j.1432-2277.2010.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation and vascular tumours

Abstract: Summary Based on analysis of the literature and of the audited ELITA (European Liver Intestinal Transplant Association)–ELTR (European Liver Transplant Registry) data, the place of liver transplantation (LT) in the treatment of vascular tumours is discussed. Hepatic epithelioid haemangioendothelioma has currently become a good indication for LT with 5‐ and 10‐year post‐LT patient survival rates of 83% and 74% respectively and 5‐ and 10‐year recurrence‐free survival rates of 82% and 64% respectively. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…At our center, all 3 children with embryonal sarcoma and 1 with rhabdoid sarcoma are alive and disease‐free 5 years after LT, corroborating multicenter results (Table ). The only mortality was a child transplanted for angiosarcoma of the liver, for which the prognosis remains poor historically . Survival after LT for metastatic neuroendocrine tumors was similarly excellent.…”
Section: Discussionmentioning
confidence: 99%
“…At our center, all 3 children with embryonal sarcoma and 1 with rhabdoid sarcoma are alive and disease‐free 5 years after LT, corroborating multicenter results (Table ). The only mortality was a child transplanted for angiosarcoma of the liver, for which the prognosis remains poor historically . Survival after LT for metastatic neuroendocrine tumors was similarly excellent.…”
Section: Discussionmentioning
confidence: 99%
“…Liver transplant has also been abandoned because of high recurrence rate and poor posttransplant survival . According to European Liver Transplant Registry experience, PHA is an absolute contraindication to liver transplant; the median overall survival of 22 patients who underwent liver transplant is 6 months, five (23%) patients died of infectious complications and 17 (77%) patients died of tumor recurrence . It is a disappointing outcome for the limited organ resource.…”
Section: Treatment Of Phamentioning
confidence: 99%
“…50 According to European Liver Transplant Registry experience, PHA is an absolute contraindication to liver transplant; the median overall survival of 22 patients who underwent liver transplant is 6 months, five (23%) patients died of infectious complications and 17 (77%) patients died of tumor recurrence. 50,51 It is a disappointing outcome for the limited organ resource. Maluf et al thought that the possibility of diffuse liver lesions (hepatocellular carcinoma, angiosarcoma, etc.)…”
Section: Treatment Of Phamentioning
confidence: 99%
“…Our experience is that surgical excision improves local PFS compared to active surveillance when disease burden is assessed, but distal PFS is similar. A number of retrospective studies have reported the outcome of EHE patients treated with liver transplantation (LT) (6)(7)(8). These studies are limited by an inherent selection bias and their retrospective nature.…”
Section: Discussionmentioning
confidence: 99%